Association of plant-based diets with adropin, atherogenic index of plasma, and metabolic syndrome and its components: A cross-sectional study on adults - Farnaz Shahdadian; Parvane Saneei; Keyhan Lotfi; Awat Feizi; Gholamreza Askari; Sayyed Morteza Safavi (Frontiers in Nutrition, 2023)
BackgroundLittle is known about the association of plant-based diet indices with metabolic syndrome (MetS) and its novel predictive biomarkers, including the atherogenic index of plasma (AIP) and adropin. We aimed to investigate the association of plant-based diets with adropin, atherogenic index of plasma, and MetS and its components in adults.MethodsThe present population-based cross-sectional study was conducted on a representative sample of adults aged 20–60 years in Isfahan, Iran. Dietary intake was obtained through a validated 168-item semi-quantitative food frequency questionnaire (FFQ). Peripheral blood was obtained after an overnight fast of at least 12 h from each participant. MetS was identified based on the Joint Interim Statement (JIS). AIP was calculated as a logarithmically transformed ratio of triglyceride (TG)/high-density lipoprotein cholesterol (HDL-c), and serum levels of adropin were measured by an ELISA kit.ResultsA total of 28.7% of subjects had MetS. No significant association was found between the overall plant-based diet index (PDI) and the healthful plant-based diet index (hPDI) with MetS. However, a non-linear association was observed between hPDI and MetS. Subjects in the third quartile of the unhealthful plant-based diet index (uPDI) had higher odds of MetS compared to the first quartile (OR: 2.39; 95% CI: 1.01, 5.66). The highest quartile of PDI (OR: 0.46; 95% CI: 0.21, 0.97) and the third quartile of hPDI (OR: 0.40; 95% CI: 0.18, 0.89) were associated with decreased odds of having high-risk AIP compared to the first quartile, after adjusting for potential confounders. No linear association was found between quartiles of plant-based diet indices and serum levels of adropin.ConclusionPlant-based diet index (PDI) and hPDI were not associated with the prevalence of MetS in adults, while moderate adherence to uPDI increased the prevalence of MetS. In addition, high adherence to PDI and moderate adherence to hPDI were associated with decreased odds of high-risk AIP. No significant association was found between plant-based diet indices and serum adropin levels. To confirm these findings, further studies with prospective designs are warranted.